Validation of the Arabic version of the general medication adherence scale in patients with type 2 diabetes mellitus in Jordan - Islam, Md. Ashraful; El-Dahiyat, Faris; Nouri, Ahmed; Alefan, Qais; Naqvi, Atta Abbas (Frontiers in Pharmacology, 2023)
Background Medication adherence is a major challenge for patients with diabetes. Adherence rates are often low, and this can lead to poor glycaemic control and increased risk of complications. There are a number of tools available to measure medication adherence, but few have been validated in Arabic-speaking populations. Aim This study aimed to validate the Arabic version of the General Medication Adherence Scale in patients with type 2 diabetes in Jordan. Methods A cross-sectional study was conducted for three months among patients attending diabetes mellitus outpatient clinic in Irbid, Jordan. The validation procedure included confirmatory factor analysis (CFA) and structure equation modelling (SEM). Fit indices, namely goodness of fit index (GFI), Tucker Lewis index (TLI), comparative fit index (CFI), and root mean square error of approximation (RMSEA) were observed. Corrected item-total correlation (ITC) was reported. Reliability was assessed using Cronbach’s alpha (α) and α value based on item deletion was also carried out. Intraclass correlation coefficient (ICC) was reported. Data were analyzed using IBM SPSS v23 and IBM AMOS v25. Results Data from 119 patients were gathered. The mean adherence score was 27.5 (± 6) ranging from 6 to 33. More than half of the patients were adherent to their therapy (n = 79, 66.4%). The reliability of the scale (n = 11) was 0.907, and ICC ranged from 0.880 – 0.930: 95% CI. The following values were observed in CFA; χ2 = 62.158, df = 41, χ2/df = 1.516, GFI = 0.913, AGFI = 0.860, TLI = 0.960, CFI = 0.971 and RMSEA = 0.066. 10 out of 11 items had corrected ITC > 0.5. The α remained between 0.89-0.92 during item deletion. Conclusion The results obtained in this study suggest that the scale is valid and reliable in measuring adherence to medications in the studied sample of patients with diabetes. This scale can be used by clinicians in Jordan to assess adherence and may further aide in evaluating interventions to improve adherence rates in persons with type 2 diabetes.